EFFECTIVENESS AND EFFICIENCY OF INTERNAL CONTROL OVER THE MANAGEMENT OF HUMAN RESOURCES OF XYZ GAS STATIONS - Felicia, Ellen; Hastuti, Theresia Dwi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
The purpose of this study was to determine the effectiveness and efficiency of internal control in managing human resources at XYZ Gas Stations. This research uses a qualitative method. This research collected primary data by conducting interviews with the Director, Manager, and Supervisor of XYZ Gas Station and documenting related files. Researchers found several problems related to human resource management such as contracts with partners and Pertamina Corporation that are not clearly managed, employees who do not carry out their job descriptions properly, inaccuracy in calculating sales rewards and ineffective HR control systems. The results of this study indicate that human resource management including internal control implemented by XYZ Gas Station has not run optimally and XYZ Gas Station must discuss with the Internal Control Unit in handling human resource management.